Analysis of Education SWOT in Indonesia in Preparing the Golden Generation of Indonesia 2045 - Dewi Nurdiyanti; Andri Hermawan; Lilis Supriatin (Jurnal Edusci, 2026)
Background. Indonesia is experiencing a strategic momentum towards Indonesia Emas 2045, a long-term vision centered on the quality of its human resources. Aims. This study aims to analyze strategies to improve the quality of education and the mastery of science and technology (IPTEK) to prepare an adaptive, competitive, and innovative generation. Methods. The method used is an exploratory qualitative approach through Focus Group Discussion (FGD) involving education stakeholders, complemented by a SWOT analysis to identify strengths, weaknesses, opportunities, and threats in the education system. Result. The results of the study indicate that the main challenges faced are disparities in educational quality across regions, low literacy in IPTEK, and a lack of integration between the curriculum and the needs of the world of work. Conclusion. Through the SWOT Analysis, the main technical priorities to be addressed include procurement of ICT devices, ongoing teacher training, equalizing infrastructure, and strengthening the vocational curriculum. Implementation. This study provides strategic recommendations for transforming the Indonesian education system to be more adaptive and aligned with the needs of the 21st century.